Electrochemical Sensor for Biological Samples Monitoring - Zabitler, Duygu; Ülker, Esra; Turan, Kübra; Erdoğan, Niran Öykü; Aydoğdu Tığ, Gözde (Topics in catalysis, 2025)
Electrochemical sensors and biosensors have attracted considerable interest due to their wide range of applications in pharmaceutical analysis, drug detection, cancer diagnosis, and monitoring toxic elements in drinking water. These sensors are characterized by their affordability, ease of manufacturing, fast response times, compact size, and ability to detect multiple analytes simultaneously. Electrochemical sensors are promising tools as they can be designed to detect a variety of analytes. Common materials employed in sensor fabrication include conducting polymers, nanomaterials, and bioreceptors. This review provides a comprehensive summary of electrochemical sensors developed for the determination of various analytes in biological samples, such as blood, plasma, serum, cerebrospinal fluid, saliva, tears, sweat, and urine. It also discusses future considerations regarding recent critical studies aimed at advancing research toward the development of novel functional electrochemical biosensors for electrochemical detection in biological samples.